Labor market policies in a Roy-Rosen bargaining economy - Hugo Jales; Zhengfei Yu (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
We study the effects of labor market policies using a bargaining model featuring compensating differentials (Rosen, 1986) and self-selection (Roy, 1951). The framework allows us to create a taxonomy of formal and informal employment. We use the model to estimate the effects of the minimum wage for the Brazilian economy using the "PNAD" dataset for the years 2001-2005. Our results suggest that, although the minimum wage generates unemployment and reallocation of labor to the informal sector, the policy might be desirable if the employment losses are concentrated in jobs characterized by low surplus.
Keywords: 330